2021
DOI: 10.1093/brain/awab217
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 stabilizes G3BP1 mRNA: relevance to amyotrophic lateral sclerosis/frontotemporal dementia

Abstract: TDP-43 nuclear depletion and concurrent cytoplasmic accumulation in vulnerable neurons is a hallmark feature of progressive neurodegenerative proteinopathies such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Cellular stress signalling and stress granule dynamics are now recognized to play a role in ALS/FTD pathogenesis. Defective stress granule assembly is associated with increased cellular vulnerability and death. Ras-GAP SH3-domain-binding protein 1 (G3BP1) is a critical stress g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…We found >2-fold higher TDP-43 protein levels in Optn 470T BMDMs, also without a change in TARDBP expression ( Figure 2 D–F), demonstrating that our findings in primary microglia were shared by other myeloid cells. TDP-43 has been shown to positively regulate one of the key proteins in stress granule formation- Ras-GAP SH3-domain-binding protein 1 (G3BP1) [ 37 ]. Given that TDP-43 protein levels in Optn 470T primary microglia were increased, we next determined whether this impacted the G3BP1 protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…We found >2-fold higher TDP-43 protein levels in Optn 470T BMDMs, also without a change in TARDBP expression ( Figure 2 D–F), demonstrating that our findings in primary microglia were shared by other myeloid cells. TDP-43 has been shown to positively regulate one of the key proteins in stress granule formation- Ras-GAP SH3-domain-binding protein 1 (G3BP1) [ 37 ]. Given that TDP-43 protein levels in Optn 470T primary microglia were increased, we next determined whether this impacted the G3BP1 protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…To pursue this further, we examined the effect of YTHDF2 knockdown in human neuron disease models. The ALS-associated TDP43(M337V) mutation was introduced into the native TARDBP locus of control human induced pluripotent stem cells (iPSCs) by CRISPR/Cas9 55 . Simultaneously, endogenous TDP43 was labeled at the C-terminus with Dendra2, facilitating identification and selection of clonal cell populations harboring the M337V mutation.…”
Section: Resultsmentioning
confidence: 99%
“…6C ). iPSCs were then differentiated into forebrain-like neurons (iNeurons) through the induced expression of master transcription factors Ngn1-2, as described previously 40,55,56 . Neurons were tracked by longitudinal microscopy over a 10d period, and their survival assessed by semi-automated tracking software developed specifically for these purposes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…That means TDP-43 can regulate stability balance in two aspects: maintain mRNA stability or promote mRNA decay. In the aspect of stability maintenance, a case reported that TDP-43 stabilizes G3BP1 transcripts by targeting a highly conserved cisregulatory element in the 3′ UTR (53). Another report also illustrated that TDP-43 mediated MTORC1-TFEB signaling by partially stabilizing RPTOR/RAPTOR to regulate autophagy (54).…”
Section: Tdp-43-mediated Mrna Stabilitymentioning
confidence: 99%